Fundamental Aspects Concerning the Validity of the Standard Equivalent Circuit for Large‐Area Silicon Solar Cells. Issue 2 (22nd December 2019) - Wagner, Jan-Martin; Carstensen, Jürgen; Adelung, Rainer
Abstract : The standard equivalent circuit of a solar cell amounts to a lumped description by separate diode and resistor elements. As its application to a large‐area silicon solar cell effectively implies averaging the emitter resistance which, however, is closely coupled to the p–n junction, it is not self‐evident that it works more or less well. Using an analytically solvable distributed series resistance model and systematically treating the deviations from the ideal case of zero emitter resistance, the equivalent circuit is found in linear order in the sheet resistivity. In this linear order, the lumped voltage losses are fully compatible with the integrated Joule losses; this compatibility turns out to be a necessary and sufficient condition for modeling the local series resistance of a large‐area silicon solar cell. In higher orders of the sheet resistivity, however, the lumped voltage losses are not compatible with the integrated Joule losses, which means that the equivalent circuit cannot describe these higher orders. The equivalent circuit resulting from the linear‐order lumped series resistance accounts for the experimentally observed variation of the lumped series resistance along the current–voltage characteristic, which turns out to be fully described by a dependence on the dark diode current only. Abstract : On analytically solving a distributed series resistance model, it is shown 1) why the equivalent circuit model holds, that is, why it is permitted to decouple series resistance and local diode effects; 2) for the equivalent circuit model to hold, it has to be modified to account for the decrease in the lumped series resistance in dependence on the dark current.